Research on decentralized control strategies for automated vehicle-based in-house transport systems: A survey - Thorsten Schmidt; K.-B. Reith; Nils Klein; M. Däumler (Logistics Research, 2020)
With the application of in-house logistics automated guided vehicle (AGV) systems for transportation three different control problems arise: task assignment, empty vehicle balancing and routing. With an increasing fleet size and especially when considering requirements like flexibility and adaptivity these control problems often become complex to solve using a central controller. The main reasons are the increasing problem size and amount of information. Decentralized control of logistics systems has received a lot of attention during the last years and may help to remedy the shortcomings of central solutions. Decentralized solutions rely on a distributed implementation for decision making and make use of local information. This survey describes basics as well as general categorizations and reviews existing decentralized control strategies for the mentioned control problems of automated in-house logistics vehicle systems. If existing, decentralized solving approaches for the control strategy problems investigated by the scientific community are listed. Additionally, these control strategies are evaluated to which extend they fulfill the requirements of the decentralized paradigm.
Keywords: 650; automated guided vehicle(AGV); decentralized control; dispatching; empty vehicle balancing; load-vehicle assignment; routing; task assignment